Preferences for long-term care insurance in China: results from a discrete choice experiment - Wang, Qun; Abiiro, Gilbert Abotisem; Yang, Jin; Li, Peng; De Allegri, Manuela (Social science & medicine, 2021)
Rapid population aging has led countries to consider the introduction of long-term care insurance (LTCI) as an essential component of a comprehensive social health protection package. Limited evidence, however, exists on people's preferences for such insurance products, especially in countries where their availability is still restricted. Using a discrete choice experiment (DCE), we investigated preferences, willingness to pay, and heterogeneity in preferences for attributes of a social LTCI among community members in China. We adopted a multi-methods approach, combining information across different data sources to identify five DCE attributes: individual premium, benefit package, coverage ceiling, government subsidy for participants, and reimbursement of home-based care provided by family caregivers. We constructed our experiment using a D-efficient design and ran the DCE survey among 1067 community members in urban and rural areas in Shenyang and Dalian, Liaoning Province from Dec 2019 to Jan 2020. We relied on a panel mixed logit model to analyze the data. Our findings indicated that people had significantly higher preferences for the LTCI product with a higher coverage ceiling, a lower individual premium, a higher government subsidy, a reimbursement of home-based care provided by family caregivers, and an expansion of the benefit package to also include necessary daily assistance. The coverage ceiling was found to be the most important attribute, followed by the reimbursement of home-based care provided by family caregivers and the individual premium. Our findings also revealed that the area of residence, prior commercial insurance ownership, age, having children, and income were the factors that drove heterogeneity in preferences for LTCIs. These findings bear important policy implications, as they provide clear guidance on product design, enabling decision-makers to increase the attractiveness and sustainability of LTCI.